ANALYTICAL METHODS DEVELOPMENT AND VALIDATION OF COMBINATION OF TWO DRUGS BY RP HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Pankaj Sharma; Dr. Rajesh Verma; Dr.Pankaj Kumar Sharma; Dr. Jaya Sharma (International Journal For Research In Biology & Pharmacy, 2023)
This research paper presents the development and validation of RP high-performance liquid chromatography (RP- HPLC) methods for the simultaneous estimation of drug combinations in marketed formulations. The study is divided into two sections, the first section describes the development and validation of an HPLC method for the simultaneous estimation of Sitagliptin & Simvastatin in marketed formulations. The second section focuses on the development and validation of an HPLC method for the simultaneous estimation of Amlodipine, HCTZ, and Valsartan in marketed formulations. Both HPLC methods undergo rigorous validation based on various parameters, including system suitability, specificity, linearity, limit of quantification (LOQ), and limit of detection (LOD). The validation results confirm the reliability and suitability of the developed methods for the simultaneous estimation of the respective drug combinations.